POTENSI AMBASSADOR PADA ASOSIASI PROFESI DI INDONESIA DALAM MENDORONG PEMENANGAN BIDDING KONFERENSI - Wardhani, Annisa Wardhani; Christina Lipuringtyas Rudatin; Heri Setyawan; Firman Syah; Muhammad Iqbal Katik Rajo Endah (Bisnis Event, 2025)
International meetings (either conferences or other forms of meetings) that are held certainly have implications for the image of the host. The organization of the event represents the destination/country that acts as the host. The potential to organize international meetings can come from several market segments, one of which is the association market segment, especially professional associations affiliated with international or world-class associations. The main reason for preparing the Ambassador Program is that the majority of international association meetings that occur periodically and alternate between countries require a kind of competitive bidding process involving local or national contacts to submit proposals or invitations (ICCA, 2012). This research was conducted to increase the number of international association conferences held in order to improve Indonesia's competitiveness as a MICE Destination. The method that will be used is the exploratory method by conducting desk research and respondent surveys to professional associations affiliated with international associations. Keyword: Ambassador Program, Bidding, Association Conference, MICE